Cyber-physical Systems Architecture for Self-Aware Machines in Industry 4.0 Environment. Issue 3 (2015) - Bagheri, Behrad; Yang, Shanhu; Kao, Hung-An; Lee, Jay
Abstract: The recently emerged methodologies for interconnected systems such as cyber-physical systems are focused to closely monitor the information and synchronize it between the physical connected systems and cyber computational space. Depending on the physical system being monitored, the approach for designing and implementing the framework for interconnect systems might differ. In manufacturing industry, utilizing advanced analytics over a systematic deployment of cyber-physical system provides network of machines with ability to perform more efficiently, collaboratively and resiliently. Such transformation can takes the manufacturing industry into the next level of evolution namely called Industry 4.0. In this paper, a unified framework for integrating CPS in manufacturing is presented. Then an adaptive clustering method as an advanced analytical method for interconnected systems will be described and at the end of the paper a case study of self-aware machines by CPS integration is presented.